2000
DOI: 10.1016/s0896-6273(00)00103-3
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation-Induced Plasticity of Orientation Tuning in Adult Visual Cortex

Abstract: A key emergent property of the primary visual cortex (V1) is the orientation selectivity of its neurons. The extent to which adult visual cortical neurons can exhibit changes in orientation selectivity is unknown. Here we use single-unit recording and intrinsic signal imaging in V1 of adult cats to demonstrate systematic repulsive shifts in orientation preference following short-term exposure (adaptation) to one stimulus orientation. In contrast to the common view of adaptation as a passive process by which re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

49
507
2
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 467 publications
(585 citation statements)
references
References 57 publications
49
507
2
1
Order By: Relevance
“…Indeed, this is exactly what experiments show [19,21]. When neurons near pinwheel centers are subjected to a pattern adaptation protocol, in which a stimulus of one orientation is presented to the receptive field of a neuron for a period of seconds to minutes, the tuning curve is altered (Fig.…”
Section: Pattern Adaptation-induced Orientation Shifts At Pinwheel Cementioning
confidence: 53%
See 1 more Smart Citation
“…Indeed, this is exactly what experiments show [19,21]. When neurons near pinwheel centers are subjected to a pattern adaptation protocol, in which a stimulus of one orientation is presented to the receptive field of a neuron for a period of seconds to minutes, the tuning curve is altered (Fig.…”
Section: Pattern Adaptation-induced Orientation Shifts At Pinwheel Cementioning
confidence: 53%
“…There is now substantial experimental support for some of the aspects of this model ( [24,37,50]; see [25] for a recent review). However, there are also numerous features of orientation tuning that this model cannot explain ( [14,21,44,52]; see [63,65] for a review). Several computational models have proposed alternate schemes, based primarily on recurrent amplification of inputs to cortex, that can largely explain the experimental data without recourse to a strict arrangement of thalamocortical projections required by the feedforward model [7,17,64].…”
Section: Orientation Tuning In Primary Visual Cortexmentioning
confidence: 99%
“…The range of A e used in our learning simulations is listed in Table 1, whereas A i was kept at zero. We were able to simulate the adaptation data of Dragoi et al (2000) by decreasing both recurrent excitatory and recurrent inhibitory connections to cells around the adapted orientation by a large fraction, i.e., by setting both A e and A i to large, positive fractional numbers. In addition, unlike the third alternative for the learning simulation mentioned above, A i had to be slightly larger than A e to simulate the adaptation data.…”
Section: Simulating Learning and Adaptation In A Recurrent Modelmentioning
confidence: 99%
“…The possible link between learning and adaptation is strengthened by an earlier psychophysical finding that adaptation, like learning, can also improve orientation discrimination at the adapted orientation, albeit only briefly (Regan and Beverley 1985). However, a recent physiological experiment on anesthetized cats by Dragoi et al (2000) showed that, unlike learning, the V1 orientation tuning curves after adaptation became broader for cells tuned around the adapted orientation. In addition, the peak of these cells' tuning curves shifted away from the adapted orientation.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation